(3NGOe GdQhVI hGdQGaYis - (3HOQ GdOjf eMeO Hf HgGOQ Hf YHO Gddg GdRQcTis; (3GdRQcTj , eMeO Hf HgGOQ Hf YHO Gddg, HOQ GdOjf CHh YHO Gddg,J (B794 (3g` s
(3ChdgG (B:s
(3CKfGA GdcdGe Ydi GdCfHI ef HGH GdjfHhY s
(3BNQgG (B:s
(3BNQ HGH GdbQV s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs